Mechanisms by Which Fermented Soybean Meal and Soybean Meal Induced Enteritis in Marine Fish Juvenile Pearl Gentian Grouper - Zhang, Wei; Tan, Beiping; Deng, Junming; Dong, Xiaohui; Yang, Qihui; Chi, Shuyan; Liu, Hongyu; Zhang, Shuang; Xie, Shiwei; Zhang, Haitao (Frontiers in Physiology, 2021)
Soy meals can cause intestinal inflammation and even injury in animals, especially infants and juvenile individuals. This study investigated the effects of fermented soybean meal (FSBM) on the growth and intestinal homeostasis of juvenile pearl gentian grouper and examined the mechanisms by which FSBM and soybean meal (SBM) induced enteritis in fish, using “3+2” full-length transcriptome sequencing. We randomly assigned 720 female juvenile groupers into three treatment groups: FM control group, 20% FSBM group (FSBM20), and FSBM40 group (n = 4). Three iso-nitrogenous (50% protein) and iso-lipidic (10% lipid) diets were prepared and fed to fish for 10 weeks. The water volume in each barrel was about 1 m3, using natural light and temperature. Results showed that dietary FSBM, at experimental level, significantly affected fish growth and intestinal structure negatively and significantly increased enteritis indices. The degree of intestinal injury and inflammation was determined by the enzyme activities of trypsin and lysozyme, and the contents of IgM, C3, C4 and malondialdehyde, and the expressions of pro-inflammatory genes (IL1β, IL8, IL17, and TNFα) and anti-inflammatory genes (IL4, IL10, and TGFβ1). Full-length transcriptome analysis identified 2305 and 3462 differentially expressed genes (DEGs) in SBM40 and FSBM40 groups, respectively. However, only 18.98% (920/5445) of DEGs had similar expression patterns, indicating that high levels of SBM40 and FSBM40 have different metabolic strategies. KEGG enrichment analysis indicated that among the significant pathways, approximately 45% were related to immune diseases/systems, infectious diseases, and signal transduction in both SBM and FSBM groups. Based on PacBio SMRT sequencing, nine toll-like receptor (TLR) members, including TLR1, TLR2, TLR3, TLR5, TLR8, TLR9, TLR13, TLR21, and TLR22, were detected in intestinal tissues of pearl gentian grouper. TLR-MyD88-NF-κB signaling pathway played an important role in the development of FSBM- and SBM-induced enteritis in pearl gentian grouper; however, TLR receptors used in SBM and FSBM groups were different. TLR1, TLR8, TLR13, and TLR22 were the main receptors used in FSBM group, while TLR5, TLR8, TLR9, TLR21, and TLR22 were the main receptors used in SBM group. Present study provides valuable theoretical references for further research on soy protein-induced enteritis in fish.